2011
DOI: 10.5502/ijw.v1i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Central Park: Nature, context, and human wellbeing

Abstract: This paper considers evidence that social and physical contexts, particularly natural environments, are surprisingly important for human wellbeing. In particular, the pursuit of happiness seems to be less a matter of individual choice than is commonly supposed. These ideas are explored through an examination of New York's Central Park.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Baumeister and Vohs (2002) put forth that ''the essence of meaning is connection'' (p. 608); various forms of connection-including a connection to nature-have been surmised to provide coherence and meaning in life. Heine, Proulx, and Vohs (2006) emphasized that meaning is found in connecting the self to the external world; consistent with this idea, Haybron (2011) suggested that nature experiences may yield meaning by their provision of ''engagement with matters of independent worth'' (p. 238). Note (2009) also made reference to the meaningfulness that can be derived from our sense of experiencing nature as an external reality with which we form an ethical, reciprocal relationship that involves transcending our immediate spatial reference.…”
Section: Meaning In Lifementioning
confidence: 91%
“…Baumeister and Vohs (2002) put forth that ''the essence of meaning is connection'' (p. 608); various forms of connection-including a connection to nature-have been surmised to provide coherence and meaning in life. Heine, Proulx, and Vohs (2006) emphasized that meaning is found in connecting the self to the external world; consistent with this idea, Haybron (2011) suggested that nature experiences may yield meaning by their provision of ''engagement with matters of independent worth'' (p. 238). Note (2009) also made reference to the meaningfulness that can be derived from our sense of experiencing nature as an external reality with which we form an ethical, reciprocal relationship that involves transcending our immediate spatial reference.…”
Section: Meaning In Lifementioning
confidence: 91%
“…Natural environments may enhance cognition and affect by improving purposefulness and fulfilment, increase ability to derive pleasure from life (Ahuvia et al 2015) and promote mutually helpful and tolerant behaviours in social interactions (Haybron 2011). These dynamics aid social group cohesion, enhance wellbeing (Haslam et al 2009) and increase stress resilience (Kelly et al 2011).…”
Section: Wellbeingmentioning
confidence: 99%
“…Rather, natural environments trigger a wide range of psychological impacts that, among other things, alter our cognitive and affective dispositionseffectively changing our programming, at least temporarily (Haybron, 2011;2014). Researchers have noted a wide range of attitudinal changes, such as a decline in materialistic values and increase in concern for others, in people exposed to natural environments.…”
Section: Mind-physical Environment (Ecological)mentioning
confidence: 99%